Leggere la biologia e la vita umana - Gatti, Maria Gabriella (Il sogno della farfalla, 2008)
Following two lines of research, one relating to biological medicine based on an experimental method and the psychiatric one which follows the deductive method starting from interpersonal relationships, the irrational and the non-conscious, the author, without referring to religion or philosophy, attempts to identify the moment in which human life starts. In order to achieve this result the morphological and functional changes of the nervous system of the foetus and the newborn are analyzed. The compatibility of data coming from the international scientific community with the psychiatrist Massimo Fagioli’s birth theory is also assessed.